Adenine nucleoside diphosphates block adaptation of mechanoelectrical transduction in hair cells. - Gillespie, P G (1993)
By adapting to sustained stimuli, hair cells in the internal ear retain their sensitivity to minute transient displacements. Because one model for adaptation asserts that this process is mediated by a myosin isozyme, we reasoned that we should be able to arrest adaptation by interfering with myosin's ATPase cycle though introduction of ADP into hair cells. During tight-seal, whole-cell recordings of transduction currents in cells isolated from bullfrog (Rana catesbeiana) sacculus, dialysis with 5-25 mM ADP gave variable results. In half of the cells examined, the rate of adaptation remained unchanged or even increased; adaptation was blocked in the remaining cells. Because we suspected that the variable effect of ADP resulted from the conversion of ADP to ATP by adenylate kinase, we employed the ADP analog adenosine 5'-[beta-thio]diphosphate (ADP[beta S]), which is not a substrate for adenylate kinase. Adaptation consistently disappeared in the presence of 1-10 mM ADP[beta S]; in addition, the transduction channels' open probability at rest grew from approximately 0.1 to 0.8 or more. Both effects could be reversed by 2 mM ATP. When used in conjunction with the adenylate kinase inhibitor P1,P5-bis(5'-adenosyl) pentaphosphate (Ap5A), ADP had effects similar to those of ADP[beta S]. These results suggest that adaptation by hair cells involves adenine nucleotides, and they lend support to the hypothesis that the adaptation process is powered by a myosin motor.